Reconsidering the contents of interpreters’ notes: A human-centered approach to classification - Sasaki, Anna (Yearbook of the Poznan Linguistic Meeting, 2020)
This paper tackles the issue of the lack of a substantially new approach to classifying the interpreters’ notes. In my paper, I highlight the fact that the researchers in the field are yet to agree on the contents of interpreters’ notes, and that is, in my opinion, the problem that is numerously stumbled upon in consecutive interpretation research in general and note-taking research in particular. Not only do researchers invent new classifications within an excising paradigm, sometimes they contradict each other presenting different definitions for the same concepts. This paper attempts to solve the issue by introducing a new perspective on the contents of interpreters’ notes by adapting the human-centered approach and turning to the “writers” of the notes, the interpreters. The interpreter trainees who participated in this research were interviewed to obtain an in-depth understanding of what is included in interpreters’ notes. Under the semiotic perspective, which assumes both linguistic and non-linguistic notes as a system of signs, I classified the interpreters’ notes based on the subject’s comments to the notes they had written. This retrospective approach unveiled how interpreter trainees perceive their notes which prompt meaning-making and facilitate the memory when delivering interpretation.